Realizing the SDGs Through Education: The Influence of Poverty and GRDP on the Average Years of Schooling in Sleman Regency - Shafira, Nadia Ayu; Prakoso, Albrian Fiky; Kurniawan, Riza Yonisa; Musfidah, Heny; Fajri, M. Arfan (IKIP Widya Darma Surabaya, 2026)
Objective: The 2022 PISA scores, which placed Indonesia 69th out of 80 countries and sixth among ASEAN nations, demonstrate that the quality of education in Indonesia still needs to be improved and that equal distribution to several remote areas must be carried out. Improving the quality of education aligns with global goals in SDG 1 (No Poverty) and SDG 8 (Decent Work and Economic Growth) because educational enhancement can reduce poverty rates and increase labor productivity. This research aims to analyze the influence of the poverty rate variable (X1) and GRDP (X2) on the average years of schooling in Sleman Regency for the 2015-2024 period. This research type uses a quantitative descriptive approach with secondary data obtained from bps.go.id for Sleman Regency. Method: The data analysis in this study employed a multiple linear regression method (Ordinary Least Squares or OLS) using EViews 12 software. Results: The results indicate that, both simultaneously and partially, the poverty rate does not exert a signify can’t yet positive influence. This can be attributed to the existence of educational assistance and policies from the Sleman Regency government that support underprivileged communities. In contrast, the GRDP variable has a significant and positive effect, both simultaneously and partially. This is because the rate of economic growth encourages individuals to pursue higher levels of education. Therefore, policies focused on poverty reduction and enhancing economic growth are necessary to enable underprivileged communities to access higher education. Novelty: To date, no previous studies have examined the effect of poverty levels and GRDP on average length of schooling. Most other studies have focused on the provincial level, and none have simultaneously examined the variables of poverty levels and GRDP on average length of schooling in Sleman Regency for the period 2015-2024.